Optimization of Company Performance Against Improvement Corporate Key Performance Indicators (KPI).Based on the Balanced Scorecard at the Head Office of PT Pelindo Jasa Maritim - Ina Novitawati (Scientia Human Capital and Organizational Behavior, 2023)
With the recovery of economic growth and the Covid-19 vaccination, it is predicted that growth will continue. This optimism is influenced by the Government's continued fiscal stimulus support for the PEN Program and economic stability that is strong enough to support current economic growth. PT Pelindo Jasa Maritim continues to strive for effective and efficient business management with an improvement orientation. The Board of Directors' Performance Assessment is a formal system used to evaluate the performance of the Board of Directors in accordance with predetermined work standards. Performance appraisal can provide an opportunity for the Board of Directors to take corrective actions with the aim of increasing the electability of the company, Directors must be able to overcome challenges and meet customer needs with a series of strategic steps that can help the company fully take advantage of the changes that occur while balancing risks to accelerate growth, so as to produce good performance in accordance with the strategies and targets that have been set. PT Pelindo Jasa Maritim as a professional company, carries out sustainable human resource management and development through increasing international standard human resource qualifications, increasing employee welfare that supports company performance and organizational development that is tailored to the needs and challenges faced by the company as well as implementing a Corporate performance appraisal system (Key Performance Indicator). consists of the following 5 (five) perspectives: Perspective of Economic and Social Value for Indonesia, Perspective of Business Model Innovation, Perspective of Technology Leadership, Perspective of Increasing Investment, Perspective of Talent. Based on the background described above, the researcher can formulate the problems that will be discussed in this study, namely: Optimization of Company Performance on the Improvement of Corporate Key Performance Indicators (KPI) Based on Balanced Scorecard. Based on the SWOT analysis for calculating the SWOT analysis the internal factor of the Marine, Equipment and Port Service cluster is 19, which means that the overall strength of the SPJM is greater than its weaknesses. While the external analysis consists of opportunities (opportunities) and threats (threats) is 8 which means the overall strength is greater than the weaknesses. From the results of the mapping of external and internal conditions, they are in the Growth quadrant, where companies must be able to optimize their strengths to be able to capture all the opportunities that exist in the industry. The position in the TOWS analysis is in the growth quadrant which is very close to the axis lines due to weaknesses that can impact on not being optimal in capturing future opportunities. Based on the TOWS Mapping Matrix, it is in the Growth quadrant, SO Strategy is the main choice while the WO Strategy is taken as a step in consolidating the internal SPJM post-merger. WO Strategy is taken as a step to improve internal weaknesses so that opportunities can be utilized optimally.